OPTIMALISASI ASPEK OPERASIONAL LAYANAN LUMPUR TINJA TERJADWAL (LLTT) IPLT SUPIT URANG - Safitri Mustika Wati (ENVIROSAN : Jurnal Teknik Lingkungan, 2022)
Humans digest food into feces that need to be excreted. The feces from the latrines should be channeled into the septic tank so as not to pollute the environment. The content of pathogens in feces is very high and can interfere with human health if it is not processed. IPLT is an integrated building designed to process excrement so that it can be discharged into water bodies or the environment. IPLT Supit URang is one of the faecal sludge processing installations for residents of Malang City. IPLT Malang City provides desludging through the LLTT program. However, the operational aspect of the LLTT IPLT Supit Urang still has not reached the target set by the Malang City government which affects the feces processing process. So that it is necessary to optimize the operational aspects of the Supit Urang LLTT IPLT so that the fecal sludge management process can run well. The method for optimizing operational aspects is to perform calculations from the stage of operation scale to operation simulation. So the operational aspects of the LLTT IPLT Supit Urang limit the service area to a maximum distance of 10 km from the IPLT location.